COMPARISON OF ELECTION OF LOCAL HEAD BEFORE AND AFTER AMENDMENT TO THE 1945 CONSTITUTION - Yulia Susantri (Syiah Kuala Law Journal, 2022)
The election of local heads (KDH) is a democratic process that must be carried out to determine who will lead the regions and determine the management of the state in the regions so that the aspirations of the people are achieved. The history of the election of KDH from year to year, both before the amendment to the 1945 Constitution and after, is interesting to explore to find out the intent and purpose of the legislators. This type of research is a normative research that portrays law as a prescriptive discipline which only looks at the law from the point of view of its norms. The data that has been obtained will be analyzed in a normativequalitative manner, namely by interpreting and constructing statements contained in documents and laws and regulations. The results showed that prior to the amendment to the 1945 Constitution, the mechanism for regional head elections was not contained in the Constitution. The election method for KDH from 1974 followed the nuances of democracy at that time. In 1974 where Pancasila democracy was implemented, the appointment of KDH was the authority of the president together with the DPRD. At the beginning of the reform era, democracy was implemented making the KDH election mechanism the full authority of the DPRD due to the demands for reform to involve wider community participation in KDH elections. Starting in 2007 after the amendment to the 1945 Constitution, the election of KDH was carried out using a direct election mechanism by the people. Various new arrangements emerged in accordance with political and social developments such as the simultaneous election of KDH, individual candidates and single candidates in the implementation of KDH elections